The box and the dragonfly - Sanders, Ted (Harper, an imprint of HarperCollins Publishers, 2015)
Horace F. Andrews, armed with a strange wooden box, and Chloe Burke, wearing a mysterious dragonfly pendant, become entangled in a secret and ancient society striving to protect powerful devices from the evil Riven
Keywords: Magic; Secret societies; Amulets; Space and time